Indicators of dental diseases, characteristics of clinical picture and methods of orthopaedic treatment of periodontal diseases in patients with diabetes mellitus (literature review) - Hermanchuk, S. (Actual Dentistry, 2018)
Summary. The analysis of scientific publications of foreign and domestic authors on the indicators of dental diseases, characteristics of the clinical picture and methods of orthopaedic treatment of periodontal tissue diseases in patients with diabetes mellitus have been carried out. Literary research shows that patients with diabetes, due to the presence of a large number of pathological changes in the tissues and organs of the oral cavity, require a special approach to orthopaedic dental treatment and further rehabilitation. Modern orthopaedic dentistry is actively developing, which has led to the emergence of new methods and materials in the design of dental prostheses to replace defects in the dentition. Studies aimed at optimizing the protocols for prosthetics in patients with concomitant diabetes remain extremely relevant, since they are aimed not only at the restoration of the lost functional capacity, but also at significant improving of the patient’s life quality. Key words: diabetes mellitus, periodontal disease, bone, orthopaedic treatment.